Maternal Obesity Induces a Pro-Inflammatory Uterine Immune Response Associated with Altered Utero-Placental Development and Adverse Fetal Outcomes - Tessier, Daniel (Université d'Ottawa / University of Ottawa, 2015)
Obese pregnant women have increased risk of a number of pregnancy complications, including poor maternal health, fetal growth restriction (FGR) and fetal demise. The success of pregnancy is dependent on precise regulation of the immune response within the utero-placental environment. Rats as a model for human related pregnancy complications are beginning to be widely used because of the similarities between these species in terms of trophoblast invasion and spiral artery remodeling. However our knowledge of immune cells and cytokine localization in the rat utero-placental tissue relating to these processes is limited. Therefore our first aim was to characterize the immune cell populations, such as uterine natural killer (uNK) cells, neutrophils and macrophages in the rat utero-placental unit at two crucial gestational ages relevant to trophoblast invasion and spiral artery remodeling, gestational day (GD) 15 and GD18. In addition, we characterized the cytokine distribution of TNFα, IFNγ and IL-10 in the utero-placental tissue at both above mentioned gestational ages. Our study has demonstrated co-localization of TNFα and IFNγ with uNK cells in the perivascular region of the spiral arteries in the rat mesometrial triangle. Neutrophils were localized at the maternal fetal interface and in the spiral artery lumen of the rat mesometrial triangle at both gestational ages. TNFα and IL-10 demonstrated a temporal change in the localization from GD15 to GD18 which coincides with the leading edge of trophoblast invasion into the mesometrial triangle. The results of the current study furthers our knowledge of the localization and temporal expression of uterine immune cells and relevant cytokines, and provides a base to research the function of these immune cells and cytokines during rat pregnancy as a model to study human pregnancy and complications related to immune functions. Since obesity is associated with a peripheral and systemic pro-inflammatory state in humans, our second objective was to investigate whether maternal obesity could alter the utero-placental and systemic immune response in the rats. To characterize maternal obesity induced changes in uterine immune state we used pregnant rats fed a control diet (normal weight; CD) or a high fat diet (obese; HFD) at GD15 and GD18. We performed immunohistochemistry to localize TNFα and IL-10, and quantified the levels of TNFα, IL-1β and IL-10 in the uterine tissue by immunoassay. To assess the systemic immune state, circulating levels of pro-inflammatory cytokine MCP-1 were assessed by immunoassay. We demonstrated an increased concentration of the pro-inflammatory marker TNFα and a reduced anti-inflammatory IL-10-positive cell distribution in the rat mesometrial triangle in response to a HFD. In addition increased circulating MCP-1 was observed in the HFD-fed dams at both gestation ages. HFD induced obesity in our rat model leads to an increase in uterine and systemic pro-inflammatory markers. These markers have demonstrated the potential to alter utero-placental development. Pregnancy complications such as FGR and fetal demise have been shown to be associated with impaired placental development as a result of altered trophoblast invasion and aberrant maternal spiral artery remodeling. Therefore, our third aim was to compare these parameters between the CD-fed rats and HFD-fed rats at GD15 and GD18. Early trophoblast invasion was increased by approximately 2-fold in HFD-fed dams with a concomitant increase in the expression of matrix metalloproteinase-9 protein, a mediator of tissue remodeling and invasion. By late gestation reduced trophoblast invasion was observed in HFD-fed dams. Furthermore, we also observed in late gestation significantly higher levels of smooth muscle actin surrounding the uterine spiral arteries of HFD-fed dams, suggesting impaired spiral artery remodeling. We also determined the impact of human serum from obese mothers on trophoblast invasion. We compared the invasion of HTR-8/SVneo cells treated with pooled first-trimester serum from obese women with or without fetal growth restriction vs. cells treated with serum from normal-weight women with or without fetal growth restriction. First-trimester serum from obese pregnant women reduced invasion of the trophoblast cell line HTR8/SVneo compared to serum from normal-weight pregnant women. Taken together, the results of this study suggest that maternal obesity can negatively influence crucial utero-placental development processes resulting in the poor pregnancy outcomes and increased fetal demise. To summarize, the HFD increased the pro-inflammatory marker TNFα which was associated with altered trophoblast invasion profiles and impaired vascular remodeling. These disturbances in utero-placental development were also associated with decreased birth weights (indication of FGR) and increased rates of stillbirths in our obese rat model. In conclusion, we have made progress in defining the influence of maternal obesity (HFD) on utero-placental development. The importance of these studies is evident since FGR represents a leading cause of perinatal morbidity and mortality. Furthermore, FGR fetuses have an increased risk of becoming obese in their lifetime as a result of fetal programming, therefore resulting in the propagation of a transgenerational obesity cycle. Therefore by understanding the mechanisms by which maternal obesity influences utero-placental development leading to FGR, we may be able to impact short term morbidity and prevent the programming of obesity in future generations. In addition, characterization of maternal obesity’s influence on utero-placental development will also help in the search for therapeutics or intervention strategies to help optimize fetal growth and improve pregnancy outcomes in obese women.
Keywords: Obesity; Pregnancy; Inflammation; Spiral artery remodeling; Trophoblast invasion